The mathematics performance of accelerated and non-accelerated freshmen in two Catholic hign schools in Metro Manila - Guieb, Corazon B.
The purpose of this study was to find out whether there is a difference between the mathematics performance of accelerated and non-accelerated freshmen in two Catholic high schools in Metro Manila. It looked into the characteristics of the students in the two groups, their attitudes toward mathematics, school and their teachers, and the relationships of these variables to their achievement. The subjects of this study consisted of 145 second year students, 71 accelerated and 74 non-accelerated, selected through random sampling from two private Catholic high schools in Metro Manila. The instruments used were (1) an achievement test in mathematics; (2) a questionnaire on student characteristics and attitudes; and (3) student's official records. Means, standard deviations and t-test were used to determine differences between the two groups. The Pearson product moment correlation technique was used to determine relationships between variables. Stepwise multiple regression analysis was used to determine student characteristics that are associated with their performance in mathematics. The study revealed the following: 1. The student's ages range from 12 to 15. The approximate monthly income of their parents ranged from P2,000 to above P20,000. Most of the parents belong to the middle social class. From the accelerated students, 98.6% of the parents are college graduates compared to 95.9% of the parents of the non-accelerated students.